Herpetological diversity in Calakmul, Campeche, Mexico: species list with new distribution notes - José António L. Barão-Nóbrega; Pedro E. Nahuat-Cervera; Ignazio Avella; Griffin Capehart; Beau Garcia; Joseph Oakley; Alexandros Theodorou; Kathy Y. Slater (Revista Mexicana de Biodiversidad)
The herpetofauna occurring in the Selva Maya is one of the richest assemblages in the Americas.